What Are the Factors Affecting Total Sleep Time During Video Polysomnography in Infants? - Paul, Grace R.; Hayes, Don, Jr.; Tumin, Dmitry; Gulati, Ish; Jadcherla, Sudarshan; Splaingard, Mark L. (American Journal of Perinatology, 2020)
Objective The aim of the study is to investigate factors affecting total sleep time (TST) during infant polysomnography (PSG) and assess if <4 hours of TST is sufficient for accurate interpretation.Study Design Overall, 242 PSGs performed in 194 infants <6 months of chronological age between March 2013 and December 2015 were reviewed to identify factors that affect TST, including age of infant, location and timing of study, presence of medical complexity, and presence of nasal tubes. A continuum of apnea-hypopnea index (AHI) in relation to TST was reviewed. Data were examined in infants who had TST <4 hours and low AHI.Results Greater TST (p < 0.001) was noted among infants during nocturnal PSGs, at older chronological and post-menstrual ages, and without medical complexity. The presence of nasogastric/impedance probes reduced TST (p = 0.002). Elevated AHIs were identified even in PSGs with TST <4 hours. Short TST may have affected interpretation and delayed initial management in one infant without any inadvertent complications.Conclusion Clinical factors such as PMA and medical complexity, and potentially modifiable factors such as time of day and location of study appeared to affect TST during infant PSGs. TST < 4 hours can be sufficient to identify high AHI allowing physician interpretation.Key Points
Keywords: infant; polysomnography; total sleep time; sleep disordered breathing